Dusting Tommy’s and Grace’s Portfolios: A Document Analysis of L2 English Learners’ Language Learning Strategies - Lei, Jiun-Iung (Widya Mandala Catholic University Surabaya, 2018)
In the field of language learning strategies, Griffiths and Oxford (2014) suggested that more qualitative studies need to be conducted as a supplement to the mainstream survey research. These qualitative methods might include interviews, think-aloud protocols, diaries, observation, and so on. Nevertheless, few studies use document analysis as a method. At best, it is marginalized as a supplement to other qualitative methods (Ahmed, 2010). This study intended to depict the process of L2 English learners’ strategy use by utilizing document analysis as a major method. In-depth interviews were conducted to corroborate the document analysis as a means of triangulation. In order to identify the learners’ strategies, the Strategy Inventory for Language Learning (Oxford, R. L., 1990) was employed as the coding scheme. The data from the interviews and documents yielded major themes and case examples.